2017
DOI: 10.3390/app7080816
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Energy Efficiency of a Pneumatic Booster Regulator with Energy Recovery

Abstract: Pneumatic booster regulators (PBR) are in great demand in modern pneumatic systems for their energy-saving abilities. A new booster regulator with energy recovery (VBA-R) was proposed, and its energy efficiency was investigated by introducing the concept of air power. On the basis of quality-alterable gas thermodynamics, an energy efficiency assessment and pressure response model for VBA-R was proposed. First, a model was solved using MATLAB/Simulink software, and an alternative experiment was designed to veri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The state of art in the field of energy efficiency of pneumatic control systems shows that many authors have made efforts to achieve improvements concerning energy efficiency of pneumatic systems in order to reduce costs and reduce energy consumption in different ways, such as the development of new control algorithms and schemes, reducing air leakage, etc. In accordance with what has been previously mentioned, a newly developed booster valve was proposed in [17,18], with the possibility of collecting and reusing compressed air energy in order to reduce the compressed air consumption. Another possible scheme, containing a fast switching on/off valve, was introduced in [19].…”
Section: Energy Efficiency Of Compressed Air Systemsmentioning
confidence: 89%
“…The state of art in the field of energy efficiency of pneumatic control systems shows that many authors have made efforts to achieve improvements concerning energy efficiency of pneumatic systems in order to reduce costs and reduce energy consumption in different ways, such as the development of new control algorithms and schemes, reducing air leakage, etc. In accordance with what has been previously mentioned, a newly developed booster valve was proposed in [17,18], with the possibility of collecting and reusing compressed air energy in order to reduce the compressed air consumption. Another possible scheme, containing a fast switching on/off valve, was introduced in [19].…”
Section: Energy Efficiency Of Compressed Air Systemsmentioning
confidence: 89%
“…At present, it is well known (and it was proved) that a polytropic process with a variable polytropic index for describing operation of the pneumatic actuator is the most proper process. Paper [7] draws attention to the fact that irrational use of the increased pressure level leads to the growth of power input. It is suggested that in a necessity, pressure to the consumer should be reduced or, conversely, use of a local device similar to a hydraulic multiplier is advisable if a higher pressure is required.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Al-Dakkan et al [2] presented a method of energy saving in the context of a servo-controlled pneumatic actuator. Yang et al [3,4] proposed a new booster valve with energy recovery for improving the energy efficiency of a pneumatic actuator system. Luciano et al [5] introduced an alternative scheme with a fast switching on/off valve interconnecting the cylinder chambers, for reducing the consumption of compressed air in pneumatic positioning systems with external loads.…”
Section: Introductionmentioning
confidence: 99%
“…All of the previous papers dealt with the problem of increasing the energy efficiency of pneumatic systems in various ways. Some of them proposed new booster valves [3,4]. Others reused exhaust air from one pneumatic component to the same component [5,[8][9][10]15,16] or another component [6,15].…”
Section: Introductionmentioning
confidence: 99%